Atomistic simulations of nanoindentation response of irradiation defects in Iron - M. Mustafa Azeem,; Wang, Qingyu; Muhammad Zubair, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Radiation response of a material is a consequence of defects’ evolution in any radiation damage event. The radiation-induced defects can significantly alter the mechanical properties of a material. Radiation damage initiates from incident neutron by bombardment on solid material causing production and evolution of Frenkel defects. Since voids are formed due to aggregation of a large number of vacancies that cause dimensional changes and hence irradiation-induced swelling. In order to characterize the effect of irradiation defects, we have performed molecular dynamics (MD) simulations to investigate nanoindentation response of point defects and voids in Fe and their effects on mechanical parameters. The radial effect of voids and their interaction mechanism is also explored by nanoindentation simulation. It has been found that most of the dislocation produced are <111> and <100> during nanoindentation in all simulated models. There will be an increase in dislocation density which will harden the material and reduce its toughness. The mechanical parameters such as hardness H and reduced elastic modulus Er of irradiation defects are calculated from P-h curves. It is found that both H & Er of the point defects and voids are lower than the perfect model.